Bruxism defined and graded: an international consensus. (4th November 2012) - Lobbezoo, F.; Ahlberg, J.; Glaros, A. G.; Kato, T.; Koyano, K.; Lavigne, G. J.; de, R.; Manfredini, D.; Svensson, P.; Winocur, E.
Summary To date, there is no consensus about the definition and diagnostic grading of bruxism. A written consensus discussion was held among an international group of bruxism experts as to formulate a definition of bruxism and to suggest a grading system for its operationalisation. The expert group defined bruxism as a repetitive jaw‐muscle activity characterised by clenching or grinding of the teeth and/or by bracing or thrusting of the mandible. Bruxism has two distinct circadian manifestations: it can occur during sleep (indicated as sleep bruxism) or during wakefulness (indicated as awake bruxism). For the operationalisation of this definition, the expert group proposes a diagnostic grading system of 'possible', 'probable' and 'definite' sleep or awake bruxism. The proposed definition and grading system are suggested for clinical and research purposes in all relevant dental and medical domains.